Pengaruh Macam Media dan PGPR Terhadap Keberhasilan Stek Tanaman Karet Kebo (Ficus Elastica) - Isna Roslyana; Tri rahayu; Libria Widiastuti (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2021)
”Thispresearchpaimsptopfindpoutpthepinfluencepof various planting mediapandpthe provisionpof PGPR concentrations on the success of kebo rubber plant cuttings (Ficus elastica).”Thecstudycused thecComplete RandomIzedcDesignc(RAL) method consisting ofctwoctreatmentcfactors.”Thecfirstcfactor was thevtype ofvplanting media, which consists of 3 types (P1i:icowimanure,iP2:ogoat manure,oandoP3o:ochickenomanure).oTheosecondofactorowas the administration of PGPR consisting of 3 types (K1: 0vmlv/vL, K2 : 10vmli/iL, and K3 : 20 mli/iL).”Theiobservation parametersnconsist of the numbernof living cuttings, theblengthbofbthe shoots, theblengthiof theoroots, theonumberxof leaves, andxthe numberxof roots. Thexresultsxshowed that P1 treatmentx(feeding of cow manure) gavecthecbestcresultsconcthecnumbercof live cuttings, the lengthcofcshoots, thecnumbercofileaves, thelnumber of roots, andbtheblengthkofkthe roots. The lowest number ofklive cuttings was 2.33 (P1), while the lowest was 1.89 (P3), then the highest shoot length was 4.78 (P1), while the lowest was 3.64 (P3), then the lowest number of leaves was 5.33 (P1), while the lowest was 3.67 (P3), then the lowest number of roots was 6.89 (P1), while the lowest was 5.26 (P3). K3 treatment (pgpr concentration of 20 ml / L) gives the best results on the number ofilive cuttings, theinumberiofileaves,ithe numberiofiroots, the lengthoof the shoots, andothe lengthoof the roots. The highest shoot length was 4.48 (K3), while the lowest was 3.39 (K1), then the highest root length was 14.38 (K3), while the lowest was 9.74 (K1).”The interaction of P x K treatmentkshowedkthekbest resultskonktheknumberkof live cuttings and root length, theklengthkofkthe buds, asiwellias on theklengthkofkthekroots.”The combination of P1K3 treatment (the provision of cow manure media and PGPR concentration of 20 ml / L) provides the best results on the growth of kebo rubber cuttings.Keywords: kebo rubber plant, kinds of planting media, number of live cuttings.